Music lessons enhance executive functions in 6- to 7-year-old children. (August 2021) - Frischen, Ulrike; Schwarzer, Gudrun; Degé, Franziska
Abstract: Studies have demonstrated positive associations between music lessons and executive functions (EFs) in children. Because researchers have focused on comprehensive music lessons taught in school, it remains unclear whether pure instrumental music lessons as an extracurricular activity reveal similar results. Moreover, interventional studies reported mixed findings and there is a lack of experimental designs allowing for causal conclusions. Therefore, the aim of this study was to investigate the impact of music lessons as an extracurricular activity on EFs in children. Primary school children (N = 94) aged 6–7 years were randomly assigned to a music group, an arts group, or a waiting control group. Different measures of EFs were assessed in pre- and posttests. The results revealed an improvement in children from the music group for some components of EFs. Based on our findings we conclude that instrumental music lessons have an impact on specific EFs in children. Highlights: We investigated causal relations between musical training and EFs in children. The study followed an experimental approach with active and passive controls. Instrumental music training improves some components of EFs in 6- to 7-year-olds. Effectiveness of training might be linked to EFs developmental trajectory.